Analisis Kemiripan 20 Aksesi Temu Ireng (Curcuma aeruginosa Roxb.) Berdasarkan Warna Rimpang, Hasil Ekstrak, dan Kandungan Fitokimia - Nurcholis, Waras; Khumaida, Nurul; Syukur, Muhamad; Bintang, dan Maria (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTCurcuma aeruginosa Roxb., popularly known as “temu ireng”, is considered as a potential source of medicinal plant for pharmacological activities. However, varieties of C. aeruginosa are still limited in Indonesia so it needs more accessions for improvement and development of new varieties. Rhizome colors, phytochemical contents and extract yield from 20 promising lines of C. aeruginosa were investigated by qualitative method for rhizome colors and phytochemical contents, and maceration method using 70% ethanol for yield extract. Similarity analysis was used for cluster analysis based on rhizome colors, phytochemical contents and yield extract. Blue was the color characterization of rhizome C. aeruginosa. The extract yield for 20 promising lines of C. aeruginosa varied from 7.92 to 19.71%, with KN and BH promising lines having the lowest and highest value, respectively. All promising lines of C. aeruginosa contain saponin and triterpenoid. Based on similarity analysis, all promising lines could be divided into 3 clusters. Cluster I consisted of 14 promising lines i.e. WG, SH, KA, GD, BH, KP, NW, PW, MB, PR, PT, KN, MD, and PK. Cluster II consisted of 4 promising lines i.e. LC, CB, KL, and GK. Cluster III consisted of 2 promising lines i.e. KD and SG. Keywords: promising lines, saponin, triterpenoid